2016
DOI: 10.1016/j.kint.2015.11.026
|View full text |Cite|
|
Sign up to set email alerts
|

Eculizumab is a safe and effective treatment in pediatric patients with atypical hemolytic uremic syndrome

Abstract: Atypical hemolytic uremic syndrome (aHUS) is caused by alternative complement pathway dysregulation, leading to systemic thrombotic microangiopathy (TMA) and severe end-organ damage. Based on 2 prospective studies in mostly adults and retrospective data in children, eculizumab, a terminal complement inhibitor, is approved for aHUS treatment. Here we prospectively evaluated efficacy and safety of weight-based dosing of eculizumab in eligible pediatric patients with aHUS in an open-label phase II study. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
212
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(245 citation statements)
references
References 45 publications
19
212
0
5
Order By: Relevance
“…Patients may develop end-stage renal failure either during the first episode or after several recurrences and the disease may recur after renal transplantation. Patients were previously exclusively treated with plasma exchange or infusions but the prognosis regarding renal function and mortality was poor until the introduction of eculizumab, which was shown to be highly effective in both adults and children with aHUS [24,25]. Current international consensus (2015) recommends the start of eculizumab treatment upon diagnosis of aHUS, although treatment can be discontinued in a small subset of patients, particularly those with autoantibodies [23].…”
Section: Treatment Of Atypical Hemolytic Uremic Syndromementioning
confidence: 99%
“…Patients may develop end-stage renal failure either during the first episode or after several recurrences and the disease may recur after renal transplantation. Patients were previously exclusively treated with plasma exchange or infusions but the prognosis regarding renal function and mortality was poor until the introduction of eculizumab, which was shown to be highly effective in both adults and children with aHUS [24,25]. Current international consensus (2015) recommends the start of eculizumab treatment upon diagnosis of aHUS, although treatment can be discontinued in a small subset of patients, particularly those with autoantibodies [23].…”
Section: Treatment Of Atypical Hemolytic Uremic Syndromementioning
confidence: 99%
“…As expected, complement inhibition is effective in patients who have a mutation in complement molecules or autoantibodies against factor H. The efficacy of therapeutic complement inhibition in patients with secondary HUS has not been systematically assessed, but it has been shown to be beneficial in a number of patients who do not have a mutation in any of the studied complement proteins. 117 These include patients with autoimmunity (eg, scleroderma), 118 systemic lupus erythematosus, 119,120 or catastrophic antiphospholipid syndrome 121,122 and secondary HUS associated with postpartum period, 123 HIV infection, 124 use of cytotoxic drugs, 35 and either bone marrow or solid organ transplantation. 27,28 On the basis of these multiple single cases, it seems that complement is involved in at least some patients with secondary HUS.…”
Section: Therapeutic Complement Inhibition Provides Insight Into Pathmentioning
confidence: 99%
“…In phase 2 clinical trials, treatment with eculizumab led to a rapid increase in the platelet count and steady improvement in renal function (77,78), and it has been approved for treatment of aHUS. These studies have demonstrated the safety and efficacy of C inhibition in patients with glomerular disease, and that inhibition can be maintained chronically.…”
Section: As a Therapeutic Targetmentioning
confidence: 99%
“…Data suggest that eculizumab is superior to plasma exchange/infusion for the treatment of aHUS, although it is not effective in all patients (77,78). The response to treatment does not seem to depend upon identification of a genetic defect in a C-related gene (77,78), although a small subset of patients are resistant to the drug due to a genetic variant in the C5 gene (79).…”
Section: As a Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation